2017
DOI: 10.1001/jamainternmed.2016.9546
|View full text |Cite
|
Sign up to set email alerts
|

Association of Testosterone Replacement With Cardiovascular Outcomes Among Men With Androgen Deficiency

Abstract: IMPORTANCE Controversy exists regarding the safety of testosterone replacement therapy (TRT) following recent reports of an increased risk of adverse cardiovascular events.OBJECTIVE To investigate the association between TRT and cardiovascular outcomes in men with androgen deficiency. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study was conducted within an integrated health care delivery system. Men at least 40 years old with evidence of androgen deficiency either by a coded diagnosis and/or a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 39 publications
3
86
0
4
Order By: Relevance
“…Interestingly, in the T‐trials itself, there was a low and equal number of cardiovascular events in each group (7 in each arm) . Furthermore, retrospective case‐control studies have associated T prescriptions with a lower risk of CV events . This includes a large (n = 83 010) retrospective study in men with low T levels by Sharma et al in which the authors concluded there was a significant reduction in all‐cause mortality, myocardial infarction and stroke following normalization of T levels.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the T‐trials itself, there was a low and equal number of cardiovascular events in each group (7 in each arm) . Furthermore, retrospective case‐control studies have associated T prescriptions with a lower risk of CV events . This includes a large (n = 83 010) retrospective study in men with low T levels by Sharma et al in which the authors concluded there was a significant reduction in all‐cause mortality, myocardial infarction and stroke following normalization of T levels.…”
Section: Introductionmentioning
confidence: 99%
“…First, our method for identifying AEs may not capture all relevant events. Categorizing AEs using International Classification of Diseases, Ninth Revision, Clinical Modification codes is a conservative measure 25 that has been used in prior research, 26 and the fact that these codes were verified by independent medical record reviewers other than the treating physician reduced the likelihood of systematic bias by physician specialty. Second, our cost outcome reflects the practice of applying a year-specific cost-to-charge ratio to the total charges related to the patients’ care, but this method does not account for variation in this ratio across procedures and conditions; however, it is unclear why this method would produce any bias systematically correlated with physician specialty.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results emerged for combined stroke events exclusively (stroke and TIA HR 0.72; 95% CI 0.62-0.84) and combined cardiac events (HR 0.66; 95% CI 0.60-0.72). 18 These findings suggest support for T.…”
Section: Studies Linking Testosterone Replacement Therapy (Trt) Witmentioning
confidence: 83%
“…In a retrospective cohort study within an integrated healthcare system, the rate of composite CV events at a median follow‐up of 3.4 years for men with low T who were given TRT (n = 8808) was 16.9/1000 person‐years vs 23.9/1000 in men never given TRT (adjusted HR 0.67 for TRT group; 95% CI 0.62‐0.73). Similar results emerged for combined stroke events exclusively (stroke and TIA HR 0.72; 95% CI 0.62‐0.84) and combined cardiac events (HR 0.66; 95% CI 0.60‐0.72) . These findings suggest support for T.…”
Section: Resultsmentioning
confidence: 99%